Inverse Wave Spectral Problem with Discontinuous Wave Speed - Efendiev, R.F.; Orudzhev, H.D. (Журнал математической физики, анализа, геометрии, 2010)
The inverse problem for the Sturm{Liouville operator with complex pe- riodic potential and positive discontinuous coe±cients on the axis is studied. The main characteristics of the fundamental solutions and the spectrum of the operator are studied. The formulation of the inverse problem and a constructive procedure for its solution are given. The uniqueness theorem of the inverse problem is proven.